BL30SEC Method for Detection of Beta-Lactams in Raw Commingled Cow Milk: AOAC Performance Tested MethodSM 061902. (25th April 2020) - Markovsky, Robert J; Douglas, David W; Sullivan, Ryan; Tran, Alan C; Legg, David R; McRobbie, Lindsey W; Schwartz, Janine A; Salter, Robert S; Klass, Nicole; Knoop, Sarah; Bastin, Benjamin; Crowley, Erin; et al.
Abstract: Testing milk for antibiotics before acceptance into dairies is required by the U.S. Pasteurized Milk Ordinance. Technological advances in tests have reduced screening times and improved detection accuracy. This work describes the validation of the Charm Rapid One Step Assay Beta-Lactam 30 Second Test according to the U.S. Food and Drug Administration Center for Veterinary Medicine protocol for raw commingled milk. Milk is added to the lateral flow test strip in an incubator/reader to deliver a 30 second result. Independent laboratory validation followed sensitivity, interference, and incurred residue protocols. Sensitivity, in parts per billion (ppb = µg/kg), using a probit curve determined 90% percent detection with 95% confidence, which met National Conference of Interstate Milk Shipments (NCIMS) specifications. Six U.S. approved beta-lactam drugs were detected below, but within 50% of, target/tolerance levels for penicillin G 2.9 ppb, ampicillin 5.9 ppb, amoxicillin 5.8 ppb, cephapirin 13 ppb, cloxacillin 8.1 ppb, and ceftiofur metabolites 73 ppb. No interferences were observed from 33 animal drugs at 100 ppb, somatic cells at 1.2 million/mL, or bacterial levels of >300 000 CFU/mL. Incurred residue detection levels were similar to levels determined with the spiked parent compound. The data support NCIMS that the BL30SEC method met U.S. criteria for testing milk for beta-lactams.